The integrative design guide to green building : redefining the practice of sustainability - Reed, Bill , 1953- (A Wiley book on sustainable design, 2009)
Written for architects and the design and construction team, this is a comprehensive guide to an integrated design process to create more sustainable buildings. The book is organized in a sequence similar to that employed by conventional design, so that it can be utilized as a real-world guide